Lymph Node Cellular and Viral Dynamics in Natural Hosts and Impact for HIV Cure Strategies - Huot, Nicolas; Bosinger, Steven E.; Paiardini, Mirko; Reeves, R. Keith; Müller-Trutwin, Michaela (Frontiers in Immunology, 2018)
Combined anti-retroviral therapies (cART) efficiently control HIV replication leading to undetectable viremia and drastic increases in lifespan of people living with HIV. However, cART does not cure HIV infection as virus persists in cellular and anatomical reservoirs, from which the virus generally rebounds soon after cART cessation. One major anatomical reservoir are lymph node follicles, where HIV persists through replication in follicular helper T cells and is also trapped by follicular dendritic cells. Natural hosts of SIV, such as African green monkeys and sooty mangabeys, generally do not progress to disease although displaying persistently high viremia. Strikingly, these hosts mount a strong control of viral replication in lymph node follicles shortly after peak viremia that lasts throughout infection. Herein we discuss the potential interplay between viral control in lymph nodes and the resolution of inflammation, which is characteristic for natural hosts. We furthermore detail the differences that exist between non-pathogenic SIV infection in natural hosts and pathogenic HIV/SIV infection in humans and macaques regarding virus target cells and replication dynamics in lymph nodes. Several mechanisms have been proposed to be implicated in the strong control of viral replication in natural host’s lymph nodes, such as NK cell-mediated control, that will be reviewed here, together with lessons and limitations of in vivo cell depletion studies that have been performed in natural hosts. Finally, we discuss the impact that these insights on viral dynamics and host responses in lymph nodes of natural hosts have for the development of strategies toward HIV cure.